Explaining the race difference in prostate cancer stage at diagnosis. - Jones, Beth A; Liu, Wen-Liang; Araujo, Andre B; Kasl, Stanislav V; Silvera, Stephanie N; Soler-Vilá, Hosanna; Curnen, Mary G M; Dubrow, Robert (Cancer epidemiology, biomarkers & prevention : a publication of the American Association for Cancer Research, cosponsored by the American Society of Preventive Oncology, 2008)
Prostate cancer is the most frequently diagnosed cancer in males in the United States, accounting for an estimated 186,320 new cases in 2008. There are striking racial or ethnic differences in prostate cancer incidence and mortality rates in the United States, with Black males 1.6 times more likely to be diagnosed and 2.4 times more likely to die with prostate cancer than Whites. Stage at diagnosis is a key prognostic factor for prostate cancer survival, with African-Americans generally diagnosed at a more advanced stage. To identify factors that explain the race-stage disparity in prostate cancer, we conducted a population-based case-case study of 251 African-American (46%) and White (54%) prostate cancer cases diagnosed in Connecticut between January 1987 and October 1990. Multivariate logistic regression was used to identify potential explanatory factors, including clinical, sociodemographic, medical care, insurance, digital rectal examination screening history, and lifestyle factors. Cox proportional hazards models assessed the impact of study variables on race differences in long-term survival. Modifiable factors such as screening practice and sociodemographic factors accounted for >60% of the race difference in prostate cancer stage at diagnosis. Histologic grade (Gleason score) accounted for comparatively less. Survival analyses confirmed the importance of tumor characteristics, education, and insurance in explaining observed race differences in survival. Although cases were identified before the widespread use of prostate-specific antigen (PSA) screening, the results should also be relevant to countries that have large underserved populations and/or disparities in access to medical care and cancer screening.
Keywords: Aged; Connecticut; Ethnic Groups; Humans; Male; Middle Aged; Neoplasm Staging; Proportional Hazards Models; Prostatic Neoplasms; Registries; Risk Factors; Survival Rate